Evaluation of the Swedish National Stroke Campaign: A population-based time-series study. Issue 9 (December 2019) - Nordanstig, Annika; Palaszewski, Bo; Asplund, Kjell; Norrving, Bo; Wahlgren, Nils; Wester, Per; Jood, Katarina; Rosengren, Lars
Background: Time delay from stroke onset to hospital arrival is an important obstacle to recanalization therapy. To increase knowledge about stroke symptoms and potentially reduce delayed hospital arrival, a 27-month national public information campaign was conducted in Sweden. Aim: To assess the effects of a national stroke campaign in Sweden. Methods: This nationwide study included 97, 840 patients with acute stroke, admitted to hospital and registered in the Swedish Stroke Register from 1 October 2010 to 31 December 2014 (one year before the campaign started to one year after the campaign ended). End points were (1) proportion of patients arriving at hospital within 3 h of stroke onset and (2) the proportion < 80 years of age receiving recanalization therapy. Results: During the campaign, both the proportion of patients arriving at hospital within 3 h (p < 0.05) and the proportion receiving recanalization therapy (p < 0.001) increased. These proportions remained stable the year after the campaign, and no significant improvements with respect to the two end points were observed during the year preceding the campaign. In a multivariable logistic regression model comparing the last year of the campaign with the year preceding the campaign, the odds ratio of arriving at hospital within 3 h was 1.05 (95% confidence interval (CI): 1.00–1.09) and that of receiving recanalization was 1.34 (95% CI: 1.24–1.46). Conclusion: The Swedish National Stroke Campaign was associated with a sustained increase in the proportion of patients receiving recanalization therapy and a small but significant improvement in the proportion arriving at hospital within 3 h.